Anxieties of modern andragogy over marketization of education - Jan Saran (Wydawnictwo Naukowe Uniwersytetu Mikołaja Kopernika, 2015)
Socio-political changes after 1989 created new opportunities for the development of adult education. At that time, the condition of education was largely determined by economic factors. The ongoing economic neoliberalism has raised a lot of criticism of the market economy, including socio-humanistic terms. Since 2008, that is, in the period of economic crisis, market dominated various areas of human life spoiling values that had been considered as essential elements of the functioning of individuals and groups. Today, economics has become a study of human interaction, addressing the issue of stimuli and incentives and entering the area of the interests of education sciences. This situation is a challenge for andragogy as a sub-discipline of pedagogy on which lies the duty of taking care of the values, formulating social policies and evaluating their implementation.